Mucosal-Associated Invariant T Cells in Autoimmune Diseases - Chiba, Asako; Murayama, Goh; Miyake, Sachiko (Frontiers in Immunology, 2018)
Mucosal-associated invariant T (MAIT) cells are innate T cells restricted by MHC-related molecule 1 (MR1). MAIT cells express semi-invariant T-cell receptors TRAV1-2-TRAJ33/12/20 in humans and TRAV1-TRAJ33 in mice. MAIT cells recognize vitamin B2 biosynthesis derivatives presented by MR1. Similar to other innate lymphocytes, MAIT cells are also activated by cytokines in the absence of exogenous antigens. MAIT cells have the capacity to produce cytokines, such as IFNγ, TNFα and IL-17, and cytotoxic proteins, including perforin and granzyme B. MAIT cells were originally named after their preferential location in the mucosal tissue of the gut, but they are also abundant in other peripheral organs including the liver and lungs. In humans, the frequency of MAIT cells is high in peripheral blood, and these cells constitute approximately 5% of circulating CD3+ cells. Their abundance in tissues and rapid activation following stimulation have led to great interest in their function in various types of immune diseases. In this review, first we will briefly introduce key information of MAIT cell biology required for better understating their roles in immune responses, and then describe how MAIT cells are associated with autoimmune and other immune diseases in humans. Moreover, we will discuss their functions based on information from animal models of autoimmune and immunological diseases.